LEADING ORGANIZATION CHANGE AMONG STAR-RATED HOTEL EMPLOYEES - Abdullah, Muhammad Khairuddin Lim; Che Omar, Che Mohd Zulkifli (International Business Education Journal, 2008)
This article investigates two forms of withdrawals behaviours, that is, turnover intentions and absenteeism among hotel employees. Many hospitality managers are convinced that excessive turnover is a costly phenomenon. Employee turnover does influences company hotel performance. Similarly, absenteeism is also one of the major contributors that indirect costs such as productivity and disruption of scheduled work. However, for service organizations like hotels, the effect of turnover and absenteeism can be significant not just in terms of costs but also to the quality and continuity of service provided. Therefore, the leader must align these behaviour with organizational change in order to survive. The ability to change rapidly and continuously is not a core competence; it is also at the heart of their cultures. Mastering strategies for managing change is more important today since the rate of change is greater than at any time in history. The risk failure is greater than ever before and the tension within the workforce is great and needs constant attention. Managerial level transformation could bring changes and transformation by injecting new ideas and policies. We must understand that change is not a process that can be forced or rushed but rather must be nurtured at a rate that is appropriate for each individual involved, as well as the organizational as a whole.